Short-term extinction predicted by population viability analysis for a Neotropical salt marsh endemic bird - Sandretti-Silva, Giovanna [UNESP]; Vannucchi, Fabio Stucchi [UNESP]; Teixeira, Larissa; Tan, Tjui Yeuw; Mori, Gustavo Maruyama [UNESP]; Reinert, Bianca Luiza [UNESP]; Bornschein, Marcos R. [UNESP] (Springer Nature, 2024)
Salt marshes pose challenges for the birds that inhabit them, including high rates of nest flooding, tipping, and predation. The impacts of rising sea levels and invasive species further exacerbate these challenges. To assess the urgency of conservation and adequacy of new actions, researchers and wildlife managers may use population viability analyses (PVAs) to identify population trends and major threats. We conducted PVA for Formicivora acutirostris, which is a threatened neotropical bird species endemic to salt marshes. We studied the species’ demography in different sectors of an estuary in southern Brazil from 2006 to 2023 and estimated the sex ratio, longevity, productivity, first-year survival, and mortality rates. For a 133-year period, starting in 1990, we modeled four scenarios: (1) pessimistic and (2) optimistic scenarios, including the worst and best values for the parameters; (3) a baseline scenario, with intermediate values; and (4) scenarios under conservation management, with increased recruitment and/or habitat preservation. Projections indicated population decline for all assessment scenarios, with a 100% probability of extinction by 2054 in the pessimistic scenario and no extinction in the optimistic scenario. The conservation scenarios indicated population stability with 16% improvement in productivity, 10% improvement in first-year survival, and stable carrying capacity. The disjunct distribution of the species, with remnants concentrated in a broad interface with arboreal habitats, may seal the population decline by increasing nest predation. The species should be considered conservation dependent, and we recommend assisted colonization, predator control, habitat recovery, and ex situ conservation.
Keywords: Assisted colonization; Conservation status; First-year survival; Formicivora acutirostris; Predator control